2020
DOI: 10.1016/j.heliyon.2020.e04494
|View full text |Cite
|
Sign up to set email alerts
|

Does competition and foreign investment spur industrial efficiency?: firm-level evidence from Indonesia

Abstract: This study examines the effects of market competition and foreign direct investment on the technical efficiency of firms within the Indonesian manufacturing sector using a Stochastic Frontier Analysis. We employ a firm-level panel dataset for the period of 2010–2014, covering 400 subsectors, and employing two measures of industrial concentration as proxies for market competition. The results suggest that firms operating in less competitive sectors in Indonesia experience higher technical efficiency. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 61 publications
11
38
0
2
Order By: Relevance
“…Starting from the upper part of Table 3, the results of the production frontier show that the overall production factors (labor, capital, raw materials, and energy) have positive coefficients and significant impacts on output at a 99% significance level (or alpha 1%). Meanwhile, each production factor's coefficient is smaller than 1, which is in line with the production theory and similar to the findings in Sari et al (2016) and Esquivias and Harianto (2020). Although the functional form in this current study is different from those in Sari et al (2016) and Esquivias and Harianto (2020), the findings are similar.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Starting from the upper part of Table 3, the results of the production frontier show that the overall production factors (labor, capital, raw materials, and energy) have positive coefficients and significant impacts on output at a 99% significance level (or alpha 1%). Meanwhile, each production factor's coefficient is smaller than 1, which is in line with the production theory and similar to the findings in Sari et al (2016) and Esquivias and Harianto (2020). Although the functional form in this current study is different from those in Sari et al (2016) and Esquivias and Harianto (2020), the findings are similar.…”
Section: Resultssupporting
confidence: 88%
“…Meanwhile, each production factor's coefficient is smaller than 1, which is in line with the production theory and similar to the findings in Sari et al. (2016) and Esquivias and Harianto (2020) . Although the functional form in this current study is different from those in Sari et al.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Some scholars also agree with the existence of learning-by-exporting. Esquivias and Harianto (2020), for example, argued that export activities contribute to promoting technological progress, because export companies need to compete in foreign markets. Mazzi et al (2020) confirmed that the productivity of export companies has increased after entering the international market.…”
Section: Low-carbon Technological Innovation and Human Capital Accummentioning
confidence: 99%